Artikel IMPLEMENTASI PERATURAN WALIKOTA NOMOR 32 TAHUN 2024 PASAL 6 TENTANG PENCEGAHAN PERKAWINAN USIA ANAK DI WILAYAH KECAMATAN SEMAMPIR KOTA SURABAYA: IMPLEMENTASI PERATURAN WALIKOTA NOMOR 32 TAHUN 2024 PASAL 6 TENTANG PENCEGAHAN PERKAWINAN USIA ANAK DI WILAYAH KECAMATAN SEMAMPIR KOTA SURABAYA - Ida Fina; Wijaya, Rahmanu (Universitas Negeri Surabaya (Unesa), 2025)
Child marriage is a complex social and economic problem that requires policies from the city government to address child marriage issues. In accordance with the policy of Surabaya Mayor Regulation Number 32 of 2024 Article 6 concerning the prevention of child marriage. The purpose of this study is to determine the strategy of Semampir District, Surabaya City in implementing Surabaya Mayor Regulation Number 32 of 2024 Article 6 concerning efforts to prevent and overcome the number of child marriages. The theory used is Public Policy according to Donald S. Van Meter and Carl E. Van Horn which has six criteria, namely policy objectives, resources, characteristics of implementing agents, disposition, communication, and economic, social, and political environments. The research method with a qualitative descriptive approach is related to explaining, describing, and describing in detail the role of Semampir District, Surabaya City in preventing child marriage. The number of informants was 3 informants taken based on purposive sampling technique. Data analysis was done by snowball sampling. The results of this study indicate that the Department of Women's Empowerment and Child Protection and Population Control of Surabaya City (DP3APPKB) through Semampir District, Surabaya City has several strategic programs in preventing child marriage in Surabaya City, which consist of Marriage Dispensation Counseling, Great Parents School, socialization, Surabaya Children's Forum, UPTD PPA, and partnerships with Regional Apparatus Organizations. The program is said to be successful, because the efforts made by Semampir District, Surabaya City have decreased from 17 cases of child marriage in 2022 to 5 cases in 2025. In addition, researchers hope that the community of Semampir District, Surabaya City will be more responsive to child care patterns. Keywords : Prevention, Semampir District, Child Marriage